Lanseringen och etableringen av ett socialt problem: En analys av debatten om ledarkulturen inom svensk landslagsgymnastik i Dagens Nyheter 2012–2013 (Sociologisk Forskning, 2015)
The launching and establishment of a social problem: An analysis of the debate on Swedish national level gymnastics in Dagens Nyheter 2012-2013In 2012 Sweden’s largest daily newspaper, Dagens Nyheter, published a number of articles on the state of affairs in Swedish national level gymnastics. In these articles, ex-gymnasts, coaches, parents and physicians stepped forward and testified about recurrent wrongdoings and abuse against young (particularly) female gymnasts. In response to the criticism, the accused coaches and representatives of the Swedish Gymnastics Federation downsized or dismissed the criticism as inaccurate. This being said, and using discursive psychology and a qualitative design, this article sheds light upon this debate – by viewing it as a struggle between a hegemonic discourse of ”the goodness” of sports, on the one hand, a number of unfavorable and negative testimonies of the state of affairs in Swedish national level gymnastics on the other. More concretely, this struggle has been analyzed with regard to the discursive and rhetoric resources the involved parties’ used to pursue their claims about the state of affairs in Swedish national level gymnastics and the impact these resources had for their credibility and legitimacy. Questions were: Who is entitled ”to spell out” their view on the state of affairs within Swedish national level gymnastics? What is mediated and how? How are descriptions and accounts about reality constructed as credible and factual? It is concluded that social problems are launched via co-production; in this process, the gymnastics community, the research community, single individuals, and the media – were co-actors.